Variation Studies in Provenances and Plus Trees of Pinus roxburghii Sarg. - Sharma, Rajesh (Indian Forester, 2007)
Chir pine is an important indigenous Chir of India much valued for its timber and oleoresin. This species is the source of a variety of goods including timber for house construction, packing cases etc. However its genetic improvement studies have remained comparatively neglected. The present study was taken up to supplement earlier studies, which remained restricted mostly to provenance testing by modern techniques such as isozyme analysis for detecting systematic differences between it populations. The study is categorized into seven altitude zones representing 33 superior phenotype to examine genetic variation of plus trees, evaluate their progenies under nursery and field conditions and also to analyze genetic variation at isogyme level. The results show significant difference in height and diameter of plus trees with average trees indicating their genetic capability which is also reflected in significant variation in cone and seed characters as also in their performance in nursery and field levels. The significant difference in morphometric traits is also corroborated in higher values of heterozygosity and genetic distance for plus trees at isozyme level and predicts their potential to perform better than average trees and consequently genetic gain in breeding programmes.